The Impact of Covid-19 on Oil Market Returns: Has Market Efficiency Being Violated? - Moyo, Clement; Anyikwa, Izunna; Phiri, Andrew (International Journal of Energy Economics and Policy, 2023)
This study examines the effect of COVID-19 pandemic on the efficiency of oil markets from 2nd February 2020 to 4th August 2021. By relying on dynamic conditional correlation GARCH and Wavelet coherence techniques, we able to provide correlations between the variables across time and frequency domains. Our empirical findings point to significant yet weak correlations between COVID-19 recovery/death rates for the time period extending from early February to early May even though we observe strong correlations between WTI prices and COVID-19 health statistics in mid-April. Moreover, during this identified time period, the length of frequency cycles within the correlations decreases from 16 days to 8 days. Altogether, these findings imply that oil markets were inefficient between February and early May and have since turned market efficient for the remaining duration of the pandemic.